1972
DOI: 10.1002/jso.2930040406
|View full text |Cite
|
Sign up to set email alerts
|

Gardner's syndrome, colon cancer, and sarcoma

Abstract: Soft tissue involvement is a major component of Gardner's syndrome. While these are frequently skin inclusion cysts, some patients exhibit fibrous dysplasias. These can vary from severe fibrosis, frequently intra‐abdominal and causing bowel obstruction, to desmoid tumors and fibrosarcomas, both of which can be progressive and life threatening. This aspect of the syndrome is poorly understood, but must be carefully evaluated in selecting treatment for the associated polyposis coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Another very important observation by Jarnum and Jensen was that histologically, the polyps only showed cystic dilatation of glands with no areas of adenomatous epithelium67. In 1972, Johnson reported that the stomach and large bowel are not carpeted with adenomatous polyps as originally described, but with hamartomatous polyps75, which confirmed the original description of Jarnum and Jensen in 1966. All the above clinical characteristics have been described by multiple authors, as well as the fact that this disease spares the esophagus15,30,103.…”
Section: Cronkhite-canada Syndrome (Ccs)supporting
confidence: 66%
“…Another very important observation by Jarnum and Jensen was that histologically, the polyps only showed cystic dilatation of glands with no areas of adenomatous epithelium67. In 1972, Johnson reported that the stomach and large bowel are not carpeted with adenomatous polyps as originally described, but with hamartomatous polyps75, which confirmed the original description of Jarnum and Jensen in 1966. All the above clinical characteristics have been described by multiple authors, as well as the fact that this disease spares the esophagus15,30,103.…”
Section: Cronkhite-canada Syndrome (Ccs)supporting
confidence: 66%
“…In 1972, Johnson et al [3] published that the polyps in the stomach and large intestine are hamartomas and confirmed the description of Jarnum and Jensen.…”
Section: Historymentioning
confidence: 65%
“…110 Trauma, as from surgery, may worsen DTF, and DTF has a high risk of local recurrence after surgery ranging from about 25% to 60% at 5 years. 19,31,59,94,[111][112][113][114][115][116][117][118][119][120] Inflammation from other types of trauma also may augment or stimulate recurrence; however, DTF does not metastasize. Although a marginal resection is associated with a worse outcome than a complete resection, the nature of the surgical procedure is strongly influenced by tumor location and associated anatomical and functional consequences.…”
Section: Evidence For Clinical Treatments Of Dtfmentioning
confidence: 99%